A multidrop optical network testbed for EPON platform - Majid M.S.A.; Din N.Md.; Jamaludin Md.Z.; Al-Mansoori M.H.; Mustafa I.S.; Radzi N.A.M.; Sadon S.Kh. (2023)
In an Ethernet Passive Optical Network (EPON) environment, the Optical Line Terminal (OLT) and Optical Network Unit (ONU) are the main end components that are required for the transfer of data. For the data transmission process, a communication protocol, i.e Multi-Point Control Protocol (MPCP) is required to avoid collision of the data that travel between the OLT and ONU This paper describes an effort in developing an EPON environment with MPCP for the OLT and ONU communications. A multidrop optical network testbed was developed on a platform intergrated with PIC microcontrollers. Although the microcontrollers have some limitations, the testbed can be used to test out protocols and algorithms for the EPON environment. 2010 IEEE.